Mechanisms for ensuring the economic security of Ukraine in the context of market economy formation: strategic challenges and prospects - Papyrin , Denys (Pressing Problems of Public Administration, 2024)
The  article is devoted to the study of mechanisms for ensuring the economic security of Ukraine in the conditions of the formation of a market economy, with an emphasis on strategic challenges and development prospects. The work compares Ukraine’s approaches to ensuring economic security with other countries, such as Turkey, Kazakhstan, the Baltic states, Azerbaijan, and Israel, which are at the intersection of the geopolitical interests of major powers. First of all, the economic stability of Ukraine is analysed in the context of global challenges, such as war, inflation and currency fluctuations. According to the World Bank, Ukraine’s GDP will decline by 29.1% in 2022, the deepest drop since independence. However, in 2023, the economy showed recovery with GDP growth of 3.5%, which indicates a certain adaptability of the economic system to wartime conditions. A comparative analysis with Turkey and Israel demonstrates different approaches to ensuring economic stability, based on macroeconomic policies, investments in the technological sector and support of the national currency.The second part of the article is devoted to resource independence, in particular to the management of natural resources and the development of renewable energy sources. Ukraine has significant potential for reducing the energy intensity of the economy and increasing the share of renewable energy sources. An important example is provided by the experience of Israel and the Baltic countries, which were able to reduce their dependence on energy imports through integration into European energy systems and innovations in the field of energy saving.The last part of the article focuses on financial security, in particular strengthening the banking system and stabilizing financial markets. Ukraine demonstrates a gradual strengthening of the banking sector, but remains vulnerable to external financial shocks. A comparison with Kazakhstan, Turkey and the Baltic states shows that Ukraine needs further reforms to improve regulatory oversight, reduce the level of non-performing loans and develop financial technologies. The main conclusion is that integration with the European economic system, diversification of the economy and the introduction of innovations in the financial sector are key tasks for ensuring the long-term economic security of Ukraine. Using the experience of other countries, such as Israel and the Baltic states, can contribute to the development of effective strategies to overcome existing challenges and increase Ukraine’s competitiveness on the world stage.